New antiprotozoal agents: Synthesis and biological evaluation of different 4-(7-chloroquinolin-4-yl) piperazin-1-yl)pyrrolidin-2-yl)methanone derivatives. Issue 3 (1st February 2017) - Ansari, Mohammad Fawad; Hayat, Faisal; Inam, Afreen; Kathrada, Fatima; van Zyl, Robyn L.; Coetzee, Maureen; Ahmad, Kamal; Shin, Dongyun; Azam, Amir
Graphical abstract: Abstract: In an endeavor to develop efficacious antiprotozoal agents 4-(7-chloroquinolin-4-yl) piperazin-1-yl)pyrrolidin-2-yl)methanone derivatives (5 –14 ) were synthesized, characterized and biologically evaluated for antiprotozoal activity. The compounds were screened in vitro against the HM1: IMSS strain of Entamoeba histolytica and NF54 chloroquine-sensitive strain of Plasmodium falciparum. Among the synthesized compounds six exhibited promising antiamoebic activity with IC50 values (0.14–1.26 μM) lower than the standard drug metronidazole (IC50 1.80 μM). All nine compounds exhibited antimalarial activity (IC50 range: 1.42–19.62 μM), while maintaining a favorable safety profile to host red blood cells. All the compounds were less effective as an antimalarial and more toxic (IC50 range: 14.67–81.24 μM) than quinine (IC50 : 275.6 ± 16.46 μM) against the human kidney epithelial cells. None of the compounds exhibited any inhibitory effect on the viability of Anopheles arabiensis mosquito larvae.